2004
DOI: 10.4049/jimmunol.173.5.3535
|View full text |Cite
|
Sign up to set email alerts
|

C Protein-Induced Myocarditis and Subsequent Dilated Cardiomyopathy: Rescue from Death and Prevention of Dilated Cardiomyopathy by Chemokine Receptor DNA Therapy

Abstract: Severe experimental autoimmune myocarditis and subsequent dilated cardiomyopathy (DCM) were successfully produced in Lewis rats by immunization with recombinant cardiac C protein. Seventy-five percent of immunized rats died between days 15 and 49 postimmunization, and all of the survived rats showed typical DCM characterized by the presence of ventricular dilatation and extensive fibrosis. Immunopathological and chemokine analysis during the acute phase revealed that there were marked macrophage infiltration w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 34 publications
2
26
0
Order By: Relevance
“…myosin binding protein C (MyBPc), Cha antigen, desmin, actin, myoglobin, tubulin, and the human β1 adrenergic receptor) as a result of T. cruzi infection ( [61][62][63][64] and K. M. Bonney, unpublished results). Observations that autoimmune responses are also initiated against these antigens in susceptible mouse strains immunized with purified cardiac myosin or myosin peptides in various models of experimental autoimmune myocarditis (EAM) support this hypothesis [65,66]. Serological analysis of infected mice also indicates responsiveness to a multitude of other yet unidentified cardiac antigens [51].…”
Section: Parasite-induced Autoimmunitymentioning
confidence: 57%
“…myosin binding protein C (MyBPc), Cha antigen, desmin, actin, myoglobin, tubulin, and the human β1 adrenergic receptor) as a result of T. cruzi infection ( [61][62][63][64] and K. M. Bonney, unpublished results). Observations that autoimmune responses are also initiated against these antigens in susceptible mouse strains immunized with purified cardiac myosin or myosin peptides in various models of experimental autoimmune myocarditis (EAM) support this hypothesis [65,66]. Serological analysis of infected mice also indicates responsiveness to a multitude of other yet unidentified cardiac antigens [51].…”
Section: Parasite-induced Autoimmunitymentioning
confidence: 57%
“…Studies of Th cell subset differentiation indicate that conditions that favor Th1 differentiation, such as the presence of IL-12 during initial activation of naive CD4 ϩ T cells, also favor the expression of functional selectin ligands (8 -12) and certain chemokine receptors, especially CXCR3 and CCR5 (13). Blockage of CXCR3 prevents disease progression in a model of experimental autoimmune myocarditis (14). It was recently demonstrated that T-bet is required for the expression of CXCR3 and functional P-selectin ligands on CD4 ϩ Th cells in vitro (15).…”
Section: T-bet Controls Pathogenicity Of Ctls In the Heart By Separabmentioning
confidence: 99%
“…Experimental autoimmune carditis (EAC) that is induced in Lewis rats by immunization with C protein is a T cell-mediated disease, but various types of autoantibodies are involved for the shift from EAC to DCM (10). In addition, it was shown that several chemokines play an important role in disease progression (9).…”
Section: Ilated Cardiomyopathy (Dcm)mentioning
confidence: 99%
“…In previous studies, we have demonstrated that cardiac C protein localizes in thick filaments of cardiac muscles (8) and has a strong carditis-inducing ability (9,10). Experimental autoimmune carditis (EAC) that is induced in Lewis rats by immunization with C protein is a T cell-mediated disease, but various types of autoantibodies are involved for the shift from EAC to DCM (10).…”
Section: Ilated Cardiomyopathy (Dcm)mentioning
confidence: 99%
See 1 more Smart Citation